Marine and coastal places: Wellbeing in a blue economy. Issue 144 (June 2023) - Fudge, Maree; Ogier, Emily; Alexander, Karen A.
Abstract: Community members have interests in the development of marine industries such as characterise the blue economy agenda. One of these interests is levels of personal and community wellbeing. Governments, local authorities and marine industries are frequently confronted with conflicting values and interests when making decisions about marine industry development. Yet it is not clear how decisions can be made in ways that also focus on community members' wellbeing. Assessing wellbeing is substantively different from other aspects of development assessment as it comprises (i) subjective and (ii) relational aspects as well as (iii) material aspects. We applied this three-fold wellbeing lens to investigate the connections people make between marine places and their personal wellbeing and how people perceive changes to marine places (industry development) affects this connection. We discuss three key findings: (i) people's subjective and relational experiences of personal wellbeing in relation to marine places were more important than experiences of material aspects; (ii) the specific quality of the marine environments and the values associated with the physical environment strongly influenced people's subjective and relational wellbeing experiences; and (iii) the development of marine industries may negatively influence people's experience of wellbeing in marine places if not done in ways that are sympathetic to their connections with these marine places. We discuss these findings with respect to the marine industry development and suggest that conceptualising and assessing wellbeing using only material concepts and measures in expanding marine industries will risk missing critical information in the development of sustainable local blue economies. Highlights: Subjective and relational wellbeing experiences were more important than material. Values influenced subjective and relational wellbeing experiences. Local blue economy development must be sympathetic to place connections. Subject and relational wellbeing is critical in blue economy development.